Carbon-induced effective lipid accumulation and self-flocculation for biofuel production of Tetradesmus obliquus FACHB-12. (25th June 2022) - Mi, Yuwei; Yang, Shangru; Chen, Jiling; Li, Zhongtang; Dong, Lei; Wei, Qun; Tang, Yonghe; Ma, Xiangmeng
Abstract: Utilizing rich organic matter in wastewater for microalgae cultivation is an attractive strategy to solve the high-cost issue in microalgae biodiesel production. In this study, common carbon sources in wastewater were used as nutrients to explore their effects on biomass accumulation and lipid production of Tetradesmus obliquus FACHB-12. The highest carbon fixation (1.2 g C·L −1 ) and biomass accumulation (1.99 g L −1 ) was achieved using glucose as the only carbon source for the microalgae cultivation in the designed system. In comparison, the high flocculation efficiency (89.63%) with the addition of glycerol achieved the recovery of lipids and starch at 0.36 g L −1 and 0.023 g L −1, respectively. In addition, results revealed that microalgae cells cultured with glycerol had the highest extracellular polymers fluorescence intensity of 2.84*10 4 R.U.·g −1 . This study provides insights of common carbon sources in wastewater for culturing microalgae, which leads to the potential reduction in microalgae cultivation cost and primary dewatering cost in practice. Graphical abstract: Image 1 Highlights: Glucose was the most effective carbon to promote biomass accumulation (1.99 g L −1 ). The highest biomass recovery of 1.11 g L −1 was obtained with glycerol culture. Organic carbon stimulated the secretion of protein-like substances. The self-flocculation mechanisms enhanced with organic carbon source.